(untitled) (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted at the Seed Laboratory, Department of Agronomy, Bangladesh Agricultural University, Mymensingh during the period from September to October, 2011 to study the effect of chemical priming of seed on germination and growth of rice seedling cv. BRRI dhan 29. Seeds were soaked in 3% and 5% solutions of CaCl2, ZnSO4 and KCl for 24, 30, 36, 42, 48, 54, 60 hours, respectively. A control was maintained where seeds were subjected to no priming treatment. The experiment was laid out in a Completely Randomized Design with three replications. Primed seeds were tested for germination and vigour on sandy soil media (60:40) in petridish under field capacity. Seed quality tests included mean germination time, shoot length, shoot dry mass, root length and root dry mass. The results revealed that priming treatments had significant influence on germination and all the growth parameters of rice seedlings. Priming with 3% ZnSO4 for 30 hours showed the highest germination percentage and the lowest mean germinaion time. Priming with 5% KCl for 54 hours showed the highest root length while 5% of the same solution for 24 hours showed the highest root dry mass. On the contrary, seeds having no priming treatment showed the lowest values for germination, vigour index, shoot length,shoot dry mass, root length and root dry mass and the highest mean germination time. The present study concludes that rice seed cv. BRRI dhan29 could be primed with 3% ZnSO4 solution for 30 hours for improving germination and seedling growth. Bangladesh J. Agril. Res. 41(3): 451-460, September 2016